The money laundering market : regulating the criminal economy / edited by Killian McCarthy. - McCarthy, Killian J. (Agenda Publishing, 2018)
Global money laundering transactions are estimated to be $3.5 trillion annually. Although global spending on anti-money laundering compliance was more than $8 billion in 2017, with most countries having adopted anti-money laundering measures, less than 1 per cent of illicit financial flows are seized by authorities. This collection of essays takes an integrated look at money laundering and the challenges facing regulators in the digital age. The contributors examine the opportunities for money laundering presented by the emergence of new payment methods, such as crowdfunding and mobile payment services, the largely unregulated financial services sector of hedge funds, private equity funds and derivatives, the explosion of online gambling, and the rise of cryptocurrencies and blockchain technology. The essays show how the anonymity, irreversibility and instantaneous nature of these online transactions, outside of the traditional banking system, make them ideally suited to hide, launder and move criminal revenues. While highlighting the challenges these digital technologies present, each essay also considers some of the tools regulators have and can use to close down the opportunities for money laundering that continues to keep crime profitable and illegal activities funded.